Mark-Up and Sale:The Joyce Cult in Overdrive - Takács, Ferenc (FOCUS: Papers in English Literary and Cultural Studies, 2024)
To make my point about James Joyce and his literary cult, first I must do a little back-tracking and cover the prehistory of this paper. Joyceans, whether of the scholarly sort or of the aficionado variety, are of course familiar with the curious complex of ritualised activities, whether verbal or physical, spontaneous or organised, that surrounds, both in Ireland and on the international scene, the work, person, memory or, quite simply, the image of James Joyce. On the local level, this includes, famously, the annual celebration of Bloomsday in Dublin, complete with the accoutrements of pilgrimage, ritual procession, relic worship and the visitation of holy shrines (the latter activity includes, for many Joycean pilgrims, doing the “stations” ofthe original fictional peregrinations of Bloom and Stephen in Ulysses).